Republicanism, democracy and mixed constitution: tensions and dialogues in modern constitutionalism (Revista Direito em Debate, 2022)
This article concluded that the implementation of the mixed Constitution was established more as a response to historical and social contexts than exclusive and unilateral choices of constituents. Among the ancients, the Constitution was theorized by Aristotle as a response to the social diversity of the polis. His concern is with the common man, far from flaunting the virtue and frugality imagined by Socratic rationalism. Among the Romans, its implementation was due to the expansion of the Empire and aimed to assuage the dilemma of the plebeization of the political body. Among the federalists, it solved the dilemma of inclusiveness and moderation of power in the context of growing social equality. As a solution to moderate power, the theory of the mixed federalist Constitution was evidenced in the non-mechanical separation of powers, in which the branches of government became arenas of disputes for social forces, in order to control each other.